2005
DOI: 10.1182/blood-2004-06-2108
|View full text |Cite
|
Sign up to set email alerts
|

Increased peripheral platelet destruction and caspase-3–independent programmed cell death of bone marrow megakaryocytes in myelodysplastic patients

Abstract: To investigate underlying mechanisms of thrombocytopenia in myelodysplastic syndrome (MDS), radiolabeled platelet studies were performed in 30 MDS patients with platelet counts less than 100 ؋ 10 9 /L. Furthermore, plasma thrombopoietin and glycocalicin index (a parameter of platelet or megakaryocyte destruction) were determined. Mean platelet life (MPL), corrected for the degree of thrombocytopenia, was reduced in 15 of 30 patients (4.3 ؎ 0.9 days [mean ؎ SD] vs 6.0 ؎ 1.3, P ‫؍‬ .0003). Platelet production ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 59 publications
3
32
0
1
Order By: Relevance
“…Similarly, a recent study 34 using ISEL demonstrated apoptosis in only 4% of megakaryocytes, which were predominantly micromegakaryocytes. These findings are largely consistent with results from our own study, 19 in which MDS megakaryocytes were negative for activated caspase-3 and showed no ultrastructural features of apoptosis. The megakaryocytes demonstrated ultrastructural changes resembling necrosislike cell death, including clumping and random degradation of nuclear chromatin and cytoplasmic vacuoles ( Figure 2c and 35 Apart from inducing apoptosis, stimulation of Fas and other death receptors (i.e.…”
Section: Pcd In Mds Megakaryocytes Studies On Apoptosis Insupporting
confidence: 82%
See 2 more Smart Citations
“…Similarly, a recent study 34 using ISEL demonstrated apoptosis in only 4% of megakaryocytes, which were predominantly micromegakaryocytes. These findings are largely consistent with results from our own study, 19 in which MDS megakaryocytes were negative for activated caspase-3 and showed no ultrastructural features of apoptosis. The megakaryocytes demonstrated ultrastructural changes resembling necrosislike cell death, including clumping and random degradation of nuclear chromatin and cytoplasmic vacuoles ( Figure 2c and 35 Apart from inducing apoptosis, stimulation of Fas and other death receptors (i.e.…”
Section: Pcd In Mds Megakaryocytes Studies On Apoptosis Insupporting
confidence: 82%
“…Up to 50% of patients have a decreased platelet lifespan, suggesting that increased peripheral platelet destruction mediated by (non-)immune mechanisms might contribute to thrombocytopenia in MDS. 19 Findings that several immunomodulatory agents and splenectomy lead to an increase in platelet counts in some MDS patients may support this notion. 20,21 Decreased platelet production.…”
Section: Apoptosis In Mds: Evidence and Controversiessupporting
confidence: 58%
See 1 more Smart Citation
“…On the other hand, the thrombopenia observed in myelodysplastic patients was recently shown to be related to a necrosis-like, caspase-3-independent death of megakaryocytes (Houwerzijl et al, 2005).…”
Section: Mitochondria Caspases and Hematopoietic Cell Differentiationmentioning
confidence: 99%
“…To identify activated caspase-3 in erythroblasts from bone marrow biopsy samples, immunostaining with a rabbit polyclonal antibody (1:100; New England Biolabs, Beverly, MA, USA) was used as previously described. 8 Samples were scored as negative (that is, absence of detectable cytoplasmic staining) or positive. A total of 100 erythroblasts per sample were examined.…”
Section: Patientsmentioning
confidence: 99%